1998
DOI: 10.1074/jbc.273.22.13421
|View full text |Cite
|
Sign up to set email alerts
|

Mild Feline Mucopolysaccharidosis Type VI

Abstract: The missense mutation, L476P, in the N-acetylgalactosamine 4-sulfatase (4S) gene, has previously been shown to be associated with a severe feline mucopolysaccharidosis type VI (MPS VI) phenotype. The present study describes a second mutation, D520N, in the same MPS VI cat colony, which is inherited independently of L476P and is associated with a clinically mild MPS VI phenotype in D520N/L476P compound heterozygous cats. Biochemical and clinical assessment of L476P homozygous, D520N/L476P compound heterozygous,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Direct 32 P phosphorylation studies have demonstrated only the precur-cells but this relatively small amount of enzyme was sufficient to reduce the stored GAGs by 75%. This is in sor form of rf4S to be mannose-6-phosphorylated (31). As expected the mature 44-kDa form of rf4S was taken good agreement with the observation that less than 10% of normal activity seem to be sufficient for the up into the cells in the absence of M6P while in the presence of M6P the cell surface MPRs were blocked degradation of lysosomal storage material.…”
Section: Correction Of Storage In Naglu-deficient Mps-iiib Skin Fibrosupporting
confidence: 82%
“…Direct 32 P phosphorylation studies have demonstrated only the precur-cells but this relatively small amount of enzyme was sufficient to reduce the stored GAGs by 75%. This is in sor form of rf4S to be mannose-6-phosphorylated (31). As expected the mature 44-kDa form of rf4S was taken good agreement with the observation that less than 10% of normal activity seem to be sufficient for the up into the cells in the absence of M6P while in the presence of M6P the cell surface MPRs were blocked degradation of lysosomal storage material.…”
Section: Correction Of Storage In Naglu-deficient Mps-iiib Skin Fibrosupporting
confidence: 82%
“…The published phenotypes and implications of the L476P (c.1427 T > C) variant in ARSB that causes a severe form of MPS VI have been recognized for many years [ 10 ]. However, a second variant of ARSB was identified within the same experimental feline colony [ 11 , 12 ]. Several laboratories now offer this MPS VI D520N “mild” DNA test to the cat breeding community.…”
Section: Introductionmentioning
confidence: 99%
“…A missense mutation (c.1558G > A), inherited independently from L476P and causing an amino acid substitution of the wild type aspartic acid to an asparagine at codon 520 (D520N) was identified in the same colony (Fig. 2 ) [ 11 , 12 ]. The phenotype of the D520N variant in combination with the L476P variant was dubbed MPS VI “mild”.…”
Section: Introductionmentioning
confidence: 99%
“…The GAGs are present in various connective tissues, in particular in bone and cartilage, and skeletal disease is the predominant abnormality associated with this disorder (Crawley et al, 2003). Previous studies described a missense mutation (c. 1558 G>A) with the amino acid substitution of the wild-type aspartic acid to an asparagine at codon 520 (D520N) in a colony of Siamese cats (Crawley et al, 1998;Yogalingam et al, 1998). The ARSB D520N variant alone has no evidence of association with the disease, but in combination with the L476P variant it can result in a mild form of MPS VI (Lyons et al, 2016).…”
Section: Discussionmentioning
confidence: 99%